Measuring the Security of External Energy Supply and Energy Exports Demand in Central Asia - Akhmetov, Almaz (International Journal of Energy Economics and Policy, 2015)
Ensuring the security of the demand for energy exports and the supply of external energy is among the top priorities for Central Asian republics. This paper utilizes disaggregated Risky Energy Supply (REES) and Risky Energy Exports Demand (REED) indexes to measure the securities of energy supply and energy demand in the region. The results are compared to the indexes in the European Union (EU) and the Organization of Petroleum Exporting Countries (OPEC). Furthermore, this paper measures individual contribution of each Central Asian country to the regional risk exposure to disruptions of energy export demand and external energy supply. The REES indexes for coal and gas of Central Asian energy-importing countries are lower than in the EU, while the regional oil RESS index for oil is significantly higher than in the EU. The average REED indexes for both crude oil and gas are significantly lower than in OPEC economies. Keywords: Energy security; Central Asia; Energy export and supply. JEL Classifications: O13; P28; P48